Transnational penal cultures: new perspectives on discipline, punishment, and desistance - Miller, Vivien; Campbell, James M. (Routledge SOLON explorations in crime and criminal justice histories, 2014)
"The histories of prisons, transportation, and police are well-established fields of enquiry. In recent years scholars have begun to recognise the subjects' global dimensions and the potential for comparative studies to provide new critical insights. This book offers original and critical essays from leading scholars working on crime, police, and prisons across the continents of Asia, the Americas, Europe, Africa, and Australia. Drawing on a range of disciplinary tools and critical analyses, and utilising a comparative transnational lens, Transnational Penal Cultures explores interdisciplinary connections between, and challenges to traditional western democratic historiographies, as well as categorisations of offenders, police and ex-offenders. "--